Iron in Armenian really means a Sky Drop? - Yeghikyan, A.
In the languages of the ancient Hittites and Egyptians, and later the Greeks, iron was called celestial metal or by the close in meaning word. A browse review of iron names in several languages shows that with the exception of the mentioned three languages, in other languages the name of the iron reflects its function (hard, cutting, superpower, iron-stone, etc.) but not origin. According to the Hittite sources, iron was produced by the masters of the Hatti kingdom controlled by Hittities, located, by the way, next to the kingdom of Hayasa. Hatti adjoins the region on the southeastern coast of the Black Sea, where, according to Aristotle, the Halibs lived - craftsmen who produced the best iron. It is known that the mountain rivers of this area brought sand and accumulated in the mouths sand with a high content of magnetite, an iron-containing mineral with a lower melting point (compared to other rocks). It is this circumstance, according to geologists, that the beginning of the iron century takes place in this area in the XV-XIII centuries BC. On the basis of all of the above, the literal translation of the Armenian name of iron erkat = dropped from the sky does not seem to be meaningless. But academic philologists categorically disagree with this. In this report, a more convincing (from the astrophysicist point of view) etymology of the Armenian word erkat = er-ka = heavenly metal is proposed.
Keywords: Astronomy